A Phosphatase‐Mimetic Nano‐Stabilizer of Mast Cells for Long‐Term Prevention of Allergic Disease. Issue 8 (8th February 2021) - Lin, Peihua; Cao, Mengda; Xia, Fan; Liao, Hongwei; Sun, Heng; Wang, Qiyue; Lee, Jiyoung; Zhou, Yan; Guan, Yunan; Zhang, Cheng; Xu, Zhiqiang; Li, Fangyuan; et al.
Abstract: Allergic diseases are pathological immune responses with significant morbidity, which are closely associated with allergic mediators as released by allergen‐stimulated mast cells (MCs). Prophylactic stabilization of MCs is regarded as a practical approach to prevent allergic diseases. However, most of the existing small molecular MC stabilizers exhibit a narrow therapeutic time window, failing to provide long‐term prevention of allergic diseases. Herein, ceria nanoparticle (CeNP‐) based phosphatase‐mimetic nano‐stabilizers (PMNSs) with a long‐term therapeutic time window are developed for allergic disease prevention. By virtue of the regenerable catalytic hotspots of oxygen vacancies on the surface of CeNPs, PMNSs exhibit sustainable phosphatase‐mimetic activity to dephosphorylate phosphoproteins in allergen‐stimulated MCs. Consequently, PMNSs constantly modulate intracellular phospho‐signaling cascades of MCs to inhibit the degranulation of allergic mediators, which prevents the initiation of allergic mediator‐associated pathological responses, eventually providing protection against allergic diseases with a long‐term therapeutic time window. Abstract : Ceria nanoparticle (CeNP‐) based phosphatase‐mimetic nano‐stabilizers (PMNSs) of mast cells (MCs) are developed for allergic disease prevention. By virtue of the regenerable catalytic hotspots of oxygen vacancies on the surface of CeNPs, PMNSs can constantly modulate degranulation‐associated phospho‐signaling cascades in allergen‐stimulated MCs via the dephosphorylation of phosphoproteins, enabling the long‐term therapeutic time window for allergic disease prevention.